I Porti Romani nel Mar Rosso da Augusto al Tardo Antico Roman Ports on the Red Sea from Augustus to Late Antiquity - Dario Nappo (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2018)
This volume draws upon the scholarship on the international trade between the Roman Empire and Eastern regions such as Arabia, Ethiopia and India. Such trade has been often described by ancient sources as a flourishing and very expensive one. More in detail, the book focuses on the life and the development of the ports on the Red Sea, controlled by Rome. These ports acted for centuries as international hubs, linking points between West and East, and they were the gates though which the eastern merchandise would reach the Roman markets. Keeping these remote settlements alive required a big effort on the part of the imperial administration, and some degree of planning to choose how and when to invest in the area. So, over the centuries, the geography of such ports changed dramatically. Most works published so far have explained such changes in terms of decline and economic shrinking, due to the "late antique phase" of the Roman Empire. This monograph looks for a different explanation and stretches the analysis into the late antique period, showing hot it was not a period of decline and economic recession, but rather of reorganization. The volume aims finally to reach a new and more full level of understanding of the Roman economic policy in the Red Sea between the first century BC and the sixth AD.